The Effect of Experiential Marketing on Customer Loyalty with Satisfaction as an Intervening Variables - Elfitra Desy Surya; Bunga Aditi; Megasari Gusandra Saragih (Institute of Computer Science (IOCS), 2020)
The diversity of transportation means today requires people to be more selective in choosing a means of transportation that can meet their needs and provide many benefits in their use. This is the reason that transportation service companies are competing to attract customers to choose the means of transportation they offer by providing services that are more satisfying than competitors. The urgency of the research is that Siantar Ekspress customers are still not satisfied with the services of PT. Kereta Api Indonesia (Persero) Medan and determine the factors that cause it. The research method uses path analysis. The results showed that experiential marketing (feel and think) has a positive and significant effect on satisfaction, while relate has a negative and insignificant effect on customer satisfaction of Siantar Ekspress PT. KAI (Persero) Medan. Satisfaction, feel, and relate have a positive and significant effect on customer loyalty Siantar Ekspress PT. KAI (Persero) Medan, while Think has no positive and insignificant effect on customer loyalty of Siantar Ekspress PT. KAI (Persero) Medan. Satisfaction mediates in full mediation the influence of feel and thinks on customer loyalty Siantar Ekspress PT. KAI (Persero) Medan. While satisfaction does not mediate the effect of relate to customer loyalty Siantar Ekspress PT. KAI (Persero) Medan.